(untitled) (Comprehensive Journal of Science, 2025)
Concrete cracks are among the most significant problems that negatively affect the efficiency and structural performance of concrete structures. The width and depth of cracks are directly related to the transfer of stresses and the reduction in both compressive and flexural strength. This review study aims to present and analyze previous research related to the effect of cracks on the structural properties of concrete, with a focus on the role of repair materials, especially epoxy injection materials, in restoring compressive and flexural strength. Studies have shown that epoxy injection is effective in improving compressive strength at a crack width of 2 mm, as well as enhancing flexural strength. Other findings indicated that using the epoxy repair system Sikadur 31, followed by strengthening with carbon fibers, was highly effective in reducing deflection and achieving the highest load-carrying capacity of concrete beams. The study concluded that cracks reduce compressive strength, as a decrease of 40.93% in compressive strength was recorded. However, when epoxy was applied, compressive strength improved by reducing the loss to 8.23%. In a recent study, a comparison was made between injecting cracks with epoxy and injecting them with epoxy containing 15% bacteria, where the bacterial-enhanced epoxy achieved a recovery of total strength reaching 99.72%, while traditional epoxy injection achieved 92.44%.